Recombinant protein production in Pseudoalteromonas haloplanktis TAC125 biofilm - Calvanese M.; D'Angelo C.; Lauro C.; Tutino M. L.; Parrilli E. (Biofilm, 2024)
Biofilms have great potential for producing valuable products, and recent research has been performed on biofilms for the production of compounds with biotechnological and industrial relevance. However, the production of recombinant proteins using this system is still limited. The recombinant protein production in microbial hosts is a well-established technology and a variety of expression systems are available. Nevertheless, the production of some recombinant proteins can result in proteolyzed, insoluble, and non-functional forms, therefore it is necessary to start the exploration of non-conventional production systems that, in the future, could be helpful to produce some “difficult” proteins. Non-conventional production systems can be based on the use of alternative hosts and/or on non-conventional ways to grow recombinant cells. In this paper, the use of the Antarctic marine bacterium Pseudoalteromonas haloplanktis TAC125 grown in biofilm conditions was explored to produce two fluorescent proteins, GFP and mScarlet. The best conditions for the production were identified by working on media composition, and induction conditions, and by building a new expression vector suitable for the biofilm conditions. Results reported demonstrated that the optimized system for the recombinant protein production in biofilm, although it takes longer than planktonic production, has the same potentiality as the classical planktonic approach with additional advantages since it needs a lower concentration of the carbon sources and doesn't require antibiotic addition. Moreover, in the case of mScarlet, the production in biofilm outperforms the planktonic system in terms of a better quality of the recombinant product.